An Observational Study of Dyspnea in Emergency Departments: The Asia, Australia, and New Zealand Dyspnea in Emergency Departments Study (AANZDEM). (March 2017) - Kelly, Anne Maree; Keijzers, Gerben; Klim, Sharon; Graham, Colin A.; Craig, Simon; Kuan, Win Sen; Jones, Peter; Holdgate, Anna; Lawoko, Charles; Laribi, Said; ,
Abstract: Objectives: The objective was to describe the epidemiology of dyspnea presenting to emergency departments (EDs) in the Asia‐Pacific region, to understand how it is investigated and treated and its outcome. Methods: Prospective interrupted time series cohort study conducted at three time points in EDs in Australia, New Zealand, Singapore, Hong Kong, and Malaysia of adult patients presenting to the ED with dyspnea as a main symptom. Data were collected over three 72‐hour periods and included demographics, comorbidities, mode of arrival, usual medications, prehospital treatment, initial assessment, ED investigations, treatment in the ED, ED diagnosis, disposition from ED, in‐hospital outcome, and final hospital diagnosis. The primary outcomes of interest are the epidemiology, investigation, treatment, and outcome of patients presenting to ED with dyspnea. Results: A total of 3, 044 patients were studied. Patients with dyspnea made up 5.2% (3, 105/60, 059, 95% confidence interval [CI] = 5.0% to 5.4%) of ED presentations, 11.4% of ward admissions (1, 956/17, 184, 95% CI = 10.9% to 11.9%), and 19.9% of intensive care unit (ICU) admissions (104/523, 95% CI = 16.7% to 23.5%). The most common diagnoses were lower respiratory tract infection (20.2%), heart failure (14.9%), chronic obstructive pulmonary disease (13.6%), and asthma (12.7%). Hospital ward admission was required for 64% of patients (95% CI = 62% to 66%) with 3.3% (95% CI = 2.8% to 4.1%) requiring ICU admission. In‐hospital mortality was 6% (95% CI = 5.0% to 7.2%). Conclusion: Dyspnea is a common symptom in ED patients contributing substantially to ED, hospital, and ICU workload. It is also associated with significant mortality. There are a wide variety of causes however chronic disease accounts for a large proportion.